TeV Diffuse Emission From the Inner Galaxy - Nayerhoda, Amid; Salesa Greus, Francisco; Casanova, Sabrina (Frontiers in Astronomy and Space Sciences, 2018)
The TeV diffuse emission from the Galactic plane is produced by multi TeV electrons and nuclei interacting with radiation fields and ambient gas, respectively. Measurements of the TeV diffuse emission help constrain CR origin and transport properties. We present a preliminary analysis of HAWC diffuse emission data from the inner Galaxy. The HAWC measurements will be used to constrain particle transport properties close to the Galaxy center correlating the HAWC maps with predictions of the DRAGON code.